PENGEMBANGAN ALAT PIROLISIS SAMPAH PLASTIK SEBAGAI MEDIA BELAJAR BERBASIS LINGKUNGAN PADA MATERI SUHU DAN KALOR DI SMP KABUPATEN MUSI RAWAS - Wahyu Arini; Endang Lovisia (Jurnal Perspektif Pendidikan, 2020)
This research aims to develop a plastic waste pyrolysis tool as an environment-based learning media in SMP Musi Regency. This research is a development research. There are 3 junior high schools used, namely Air Satan Public Middle School, Muara Beliti Public Middle School and Pedang Public Middle School. Learning outcomes of learning media using pyrolysis tools by measuring students' understanding through given questions is greatly improved and average N-Gain (0.81) are included in the high category. Then for the questionnaire students' responses to the learning media pyrolysis tool obtained an average of 89,75% and a guidebook of 87,89% which is in the category of very practical, as well as a guidebook for the feasibility of the contents of 89,81%, the feasibility of serving 92,59% and language eligibility of 88,89%. For the validity level of the pyrolysis tool to the material is 90% and the media is 88,64% and for the validity of the guidebook for the material is 87,5% and the media is 84,37%. Based on the results of the analysis it can be concluded that the environment-based pyrolysis tool that was designed, developed is suitable for use as a medium for learning physics on material temperature and heat. In this research, it can also be used to produce fuel substitutes for petroleum that are difficult to renew and the impact on the environment can minimize plastic waste that is very difficult to degrade.